Korelasi Kebutuhan Kalori, Power Otot Tungkai Dan Koordinasi Mata-Kaki Dengan Hasil Lompat Jauh Pada Atlet Pelajar Sumatera Selatan - Hengki Kumbara; Sukirno Sukirno (Journal Physical Education, Health and Recreation, 2017)
This study aims to determine the relationship of nutritional status with long jump results, leg muscle power with long jump results, eye-foot coordination with long jump results. The research method is quantitative with the type of correlation. Total population of 13 athletes and samples of 13 people with total sampling technique. Data collection techniques with tests and measurements are body mass index measurements for nutritional status, standing broud jump test to measure leg muscle power, soccer wall volley test for eye-foot coordination and long jump test. The data analysis used multiple regression analysis with SPSS 20. The result showed that there was a significant correlation of X1 and Y with rcount > rtable that is 0,710 > 0,467 and Contrubution Correlation is 50,41%. There is a significant correlation of X2 and Y with rcount > ttable ie 0,608 > 0,467 Contrubution Correlation is 36,96%. There is a significant correlation of X3 and Y with rcount > rtable ie 0,724 > 0,467 Contrubution Correlation is 52,41%. There was a significant correlation between (X1, X2, X3 and Y) with fcount> ftable of 15.609 > 3.71.